THERMAL VALIDATION TESTING OF AUTOMATIC IDENTIFICATION SYSTEM (AIS) RECEIVER FOR LOW EARTH ORBIT (LEO) CUBESAT - FEBRIAN (NIM : 23215014), NAZMI
The advancements of electronics technology make the nanosatellite’s missions become more varied. One of its mission is retrieving Automatic Identification System (AIS) data from vessels on the ground. The AIS mission on satellite platform is effective to be implemented in Indonesia to monitor Indonesian’s maritime assets as global maritime fulcrum. The type of nanosatellites made in this study is a CubeSat with the size of 1.5U. This research begins with initial design of AIS receiver based on link budget calculations and followed by simulations using Advanced Design System (ADS). AIS receiver prototype has been implemented using RFIC Si4362 and MSP430G2553 Microcontroller to control the device. The main mission of AIS Receiver is to receive and decode AIS signals at the frequency of 161.975 MHz and 162.025 MHz into AIVDM NMEA0183 standard format. The decoded AIS data is sent to a Raspberry Pi Compute Module (RPICM) as On-Board Data Handling (OBDH) CubeSat before it is sent to the ground station. All of the CubeSat’s subsystem must able to pass the thermal testing before it is launched into orbit. Thermal testing is performed to observe the performance of subsystems in the extreme conditions like CubeSat conditions in the space. Thermal testing is carried out at the Satellite Technology Center (PUSTEKSAT) of National Aeronautics and Space Agency (LAPAN) facility located in Rancabungur, Bogor, West Java. The thermal test is done by running the device at the temperature of -20oC up to 60oC for 3 hours 56 minutes. Thermal testing indicates that the AIS Receiver is capable to work in the orbital temperature range. After testing, the data reception success rate reaches 36.76% with a minimum RSSI value equal to -96dBm.